Structure Activity Relationship Studies of 5-Membered Heterocyclic Derivatives - Kumudha, D. (International Journal of Pharmaceutical & Biological Archive, 2016)
Some novel 4-([5-amino-1,3,4-thiadiazol-2yl) methyl)-5-substituted phenyl-4H-1,2,4-triazol-3-thiols (8a-d), 5[(3-mercapto-5-substituted phenyl-4H-1,2,4-triazol-4-yl)methyl]1,3,4-oxadiazole-2-thiol[9a-d], 4-(5-mercapto-4-(4-substituted phenyl)-4H-1,2,4-triazol-3-yl]methyl-5-substituted phenyl-4H-1,2,4-triazole-3-thiol [10a1-a2 ?óÔé¼ÔÇ£ 10d1-d2], 2-(3-mercapto-5-substituted phenyl)-4H-1,2,4-triazol-4-yl)-N1-[(1E)-substituted phenyl methylene) acetohydrazide (Schiffs bases) [11a1-a6-11d1-d6] and 2-(3-mercapto-5-substituted phenyl-4H-1,2,4-triazol-4-yl)-N-(4-oxo-2-substituted phenyl-1,3-thiazolidin-3-yl) acetamides [12a1-a3-12d1-d3] were prepared and characterized by IR, 1H-NMR, 13C-NMR, Mass spectral analysis. Few compounds were evaluated for anticonvulsant, CNS depressant activities and neurotoxicity as reported earlier. Additionally the Structure Activity Relationship (SAR) studies have been carried out to determine the relevance of the different moieties that define the potency of triazole derivatives.